EFFICACY OF SOME ESSENTIAL OILS AGAINST STEM ROT OF GROUNDNUT (ARACHIS HYPOGAEA L.) CAUSED BY SCLEROTIUM ROLFSII (SACC.) - BASUDEB DASGUPTA; SWAGATA BARMAN; SOLANKI SARKAR; SRIKANTA DAS (The Bioscan, 2015)
The essential oils, like-Lemon grass, Citronella and its derivatives showed effective against stem rot of groundnut caused by Sclerotium rolfsii in in vitro as well as in vivo condition. The efficacy of these oils against the Sclerotium rolfsii was assessed with the inhibition percentage at very low concentration (0.0125% to 0.15%) under in vitro condition. Under in vivo condition, the seeds were soaked with the above oils with the concentration of 0.05% and 0.1% for 30-40 minutes before sowing to show the efficacy on disease mortality percentage. The result showed that all essential oils recorded the better performance, but derivatives of Citronella oil, Geraniol and Terpinoid were most effective under in vitro condition and in vivo condition. Highest disease control was recorded in treatment with terpinoid where 9.1% disease mortality was found. So, the applications of essential oils are possible by farmers for sustainable crop production through eco-friendly management that can be incorporated in Integrated Disease Management (IDM) system.